2012
DOI: 10.5430/jnep.v2n3p120
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the “lived-experience”: analysis of reports from women with systemic lupus erythematosus

Abstract: Objective: To investigate how systemic lupus erythematosus (SLE) has changed the lives of affected women and their reports on how this condition has affected them. Method:Interviews were performed in accordance with the qualitative study method of Amatuzzi and the answers were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…SLE is a source of disability that can create a burden of poor quality of life 6, 7, 8, 9, 10. The quality of life of SLE patients is always worse than that of healthy people and remains poor even in patients with SLE without complications and organ damage 6, 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLE is a source of disability that can create a burden of poor quality of life 6, 7, 8, 9, 10. The quality of life of SLE patients is always worse than that of healthy people and remains poor even in patients with SLE without complications and organ damage 6, 11.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of life of SLE patients is always worse than that of healthy people and remains poor even in patients with SLE without complications and organ damage 6, 11. The low quality of life of people with SLE seems to limit daily life activities, especially due to joint pain resulting from SLE relapses, depression and withdrawal from the environment, changes in interpersonal relationships, discrimination, difficulties in finding employment, obstacles to performing social roles, and a high risk of infertility 10, 12, 13, 14, 15, 16, 17, 18. Low quality of life because of SLE flares cannot be predicted due to the increased intensity of exposure factors 1, 19.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, 2 studies of rheumatic disease, including lupus, demonstrated that religiosity is an important active coping strategy for Latinos (36,37). Research focused on lupus patients’ attachment to spirituality/religiosity to face their illness is scarce (38,39). Additional studies have explored the concept of religion in disease beyond its role as a coping mechanism, for how the illness itself is conceived and experienced.…”
Section: Discussionmentioning
confidence: 99%